Akuntabilitas Pelayanan Publik Berbasis Aplikasi Digital pada Birokrasi Pemerintahan Daerah - Susanto, Slamet; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The digital transformation of regional bureaucracy has encouraged local governments in Indonesia to provide public services through application-based platforms. Although digitalization promises efficiency, accessibility, and transparency, it also raises issues of accountability, service reliability, unequal access, complaint handling, and personal data protection. This article examines the accountability of digital public services administered by regional governments in Indonesia. Using a normative juridical method with statutory and conceptual approaches, the study analyzes the legal basis, accountability indicators, obstacles, and strengthening strategies. The findings show that digital public services already have an adequate legal basis, but accountability remains limited due to fragmented applications, weak interoperability, unequal access, unclear service standards, and uneven data protection practices.